2014
DOI: 10.1002/jemt.22397
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of liquid crystals using cryo‐TEM: Specimen preparation and low‐dose imaging

Abstract: Liquid crystals (LCs) represent a challenging group of materials for direct transmission electron microscopy (TEM) studies due to the complications in specimen preparation and the severe radiation damage. In this paper, we summarize a series of specimen preparation methods, including thin film and cryo‐sectioning approaches, as a comprehensive toolset enabling high‐resolution direct cryo‐TEM observation of a broad range of LCs. We also present comparative analysis using cryo‐TEM and replica freeze‐fracture TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 70 publications
4
89
0
Order By: Relevance
“…Notably, chiral domains in the nematic phase of achiral compounds exhibiting dimerisation through hydrogen bonding were reported more than 15 years ago 19 ; however, such domains were found to exhibit macroscopic twist deformation of the director in the optical regime. Lastly, although the twist-bend model has been proposed 8,9,11,12,16,20 for the consistent interpretation of various experimental observations on the dimer N X phase, there is, to our knowledge, no direct identification of the heliconical structure and, furthermore, there are indications 21,22 that the dominant molecular arrangement in the N X phase could differ from that of the twist-bend model.…”
mentioning
confidence: 83%
“…Notably, chiral domains in the nematic phase of achiral compounds exhibiting dimerisation through hydrogen bonding were reported more than 15 years ago 19 ; however, such domains were found to exhibit macroscopic twist deformation of the director in the optical regime. Lastly, although the twist-bend model has been proposed 8,9,11,12,16,20 for the consistent interpretation of various experimental observations on the dimer N X phase, there is, to our knowledge, no direct identification of the heliconical structure and, furthermore, there are indications 21,22 that the dominant molecular arrangement in the N X phase could differ from that of the twist-bend model.…”
mentioning
confidence: 83%
“…Previous studies on other thermotropic bent-core LC films carried out with this instrument demonstrated the possibility to visualise smectic layers with resolution better than 0.7 nm. [22,[24][25][26] The LC samples were dissolved in chloroform, and the solution was dispersed on a TEM grid coated with plasma-treated continuous carbon film. After evaporation of the chloroform, the thickness of the LC films was between 50 and 100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The manipulation of these nanometer-size molecules into coherent, centimeter-scale structures is now routine. Although we have become adept at deducing textures indirectly through optical microscopies (1)(2)(3)(4)(5), probing the molecular-scale organization requires either a glassy material or rapid cooling of samples, providing metastable states that can be directly visualized through scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) (6)(7)(8). Although these techniques are effective to study a variety of more complex LC phases, including smectic LCs (6,7,9), cholesteric and blue phases (10), and biological LC polymers (11,12), nonglassy, low molecular weight nematic LCs (NLCs) reorient during fast freezing.…”
mentioning
confidence: 99%